PERAN HAKIM DALAM MEWUJUDKAN KEPASTIAN HUKUM BAGI MASYARAKAT PENCARI KEADILAN - Lubis, Fauziah; Sari, Annisa Jamak; Khairiah, Azra; Husna, Jamilatul; Ritonga, Rizki Abadi (Jurnal Keluarga Sehat Sejahtera, 2025)
Evidence in civil cases is an important aspect that determines the success of dispute resolution in court. This article discusses the definition of proof, the process of proof in civil trials, the types of evidence, the legal basis that regulates it, and the obstacles that are often faced in the implementation of proof. The research method used is normative legal research with a descriptive-analytical approach through literature study. The results showed that a good understanding of evidence and the support of an effective judicial system are needed so that the objectives of justice and material truth can be achieved. The evidentiary process in civil cases is an important part that determines the success of a lawsuit in court. Evidence aims to clarify the truth of the facts argued by the parties so that the judge can make a fair decision based on valid and convincing evidence. This article is expected to be useful for law students, legal practitioners, and the general public interested in civil law.